USING A META-LANGUAGE TO BRIDGE THE GAP BETWEEN NATURAL LANGUAGES AND COMPUTER LANGUAGES - Selin Temizer (Havacılık ve Uzay Teknolojileri Dergisi, 2007)
Natural languages have vast vocabularies, complex grammars and inherent ambiguities that make them difficult to be processed directly by computers, even with state-of-the-art technology. Therefore, in order to communicate with computers we need to ‘develop software’, which is actually the very process of translating our problem statements, data and solution algorithms from the languages we speak to the languages that computers speak. But software development and maintenance are costly, time consuming and have many major challenges of their own. In this document we present a group of techniques and tools, collectively named as Temizer Description System, that aim to bridge the gap between natural languages and computer languages by enabling computers to understand the logical structure of natural language texts. The main idea is to tag texts piece by piece in order to make them semantically meaningful to the computers. Once computers start figuring out the meaning of text chunks, they can also use the same chunks to talk back to us and we demonstrate how this new and effective way of communication could be used to automate (i.e. eliminate) many tedious and error-prone aspects of developing and maintaining software.